2017
DOI: 10.1101/199208
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Demonstration of the potential of environmental DNA as a tool for the detection of avian species

Abstract: Birds play unique functional roles in the maintenance of ecosystems, such as pollination and seed dispersal, and thus monitoring bird communities (e.g., monitoring bird species diversity) is a first step towards avoiding undesirable consequences of anthropogenic impacts on bird communities. In the present study, we hypothesized that birds, regardless of their main habitats, must have frequent contact with water and that tissues that contain their DNA that persists in the environment (environmental DNA; eDNA) c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Where other species of finch but no Gouldian finches were observed and counted, the finch test was positive, but the Gouldian finch test was negative. These results are very promising, considering the early stages of research on the use of eDNA for vertebrate detection in the field (Ushio et al 2017(Ushio et al , 2018. Although the test has high specificity and there were no false positive results, there were negative results for waterholes where Gouldian finches were present, indicating that the reliability and robustness of the tests still need optimisation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Where other species of finch but no Gouldian finches were observed and counted, the finch test was positive, but the Gouldian finch test was negative. These results are very promising, considering the early stages of research on the use of eDNA for vertebrate detection in the field (Ushio et al 2017(Ushio et al , 2018. Although the test has high specificity and there were no false positive results, there were negative results for waterholes where Gouldian finches were present, indicating that the reliability and robustness of the tests still need optimisation.…”
Section: Discussionmentioning
confidence: 88%
“…There is some evidence that the presence of terrestrial mammals can be determined by sampling the water bodies from which they drink (Ushio et al 2017). Only 1 study on eDNA detection of live, nonaquatic birds from water has been published to date (Ushio et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the advantage to using active user-controlled collection and aggregation methods instead of more passive approaches is that detection rates can be increased by stepping up survey effort. For example, if water bodies (ponds) are used to passively collect eDNA shed by terrestrial mammals or birds (e.g., Harper et al, 2019;Ushio et al, 2017;Ushio et al, 2018;Williams et al, 2018), then the power of the survey to detect the presence of target species is limited by the rate at which these species naturally use ponds, the rate at which they shed eDNA into these ponds, and the number of ponds in the landscape. Only a few of these rates are available for active manipulation by a surveyor, and thus even a highly sensitive eDNA assay will be limited in its detection power.…”
Section: | Discussionmentioning
confidence: 99%
“…Successful alternative approaches using eDNA to survey for terrestrial species published thus far have utilized water bodies that passively aggregate eDNA shed from target species (e.g., Harper et al, 2019;Rodgers & Mock, 2015;Ushio et al, 2017;Valentin et al, 2018;Williams et al, 2018). These range from using lotic and lentic waterbodies (Deiner et al, 2016;Harper et al, 2019;Sales et al, 2019;Ushio et al, 2017Ushio et al, , 2018 to artificial containers such as those used in Williams et al (2018) that terrestrial species use for drinking, bathing or foraging. Valentin et al (2018) devised a different eDNA approach for surveying brown marmorated stink bug (Halyomorpha halys) in agricultural produce, in which eDNA deposited by H. halys on fruits and vegetables was aggregated in the water farmers used to wash their produce and then tested to detect the eDNA left by H. halys.…”
mentioning
confidence: 99%
“…As eDNA metabarcoding has been recognized as an efficient approach in species detection and biodiversity assessment [5,[12][13][14][15]35], its use as a biodiversity monitoring tool has been increasing [12,17,36]. The authors of those monitoring studies performed periodic water samplings and generated eDNA time series, and showed that temporal fluctuations in species (or OTU) richness and detection probability of eDNA of a target taxa [12,17,36,37] were in good agreement with temporal fluctuations in other reliable data (e.g., visual census).…”
Section: Quantitative and Multispecies Fish Edna Monitoringmentioning
confidence: 99%